A Prospective Study On Response To Treatment Of Patients With Temporomandibular Disorder: A Clinical Study - Kashmoola, Muhannad Ali; Mustafa, Nazih Shaaban; Mohamed, Robiah; Mohamed Talmiz, Siti Nabilah (IIUM Medical Journal Malaysia, 2017)
Introduction: Temporomandibular joint dysfunction (TMD) is regarded as multifactorial in origin and this may influence the diagnosis and treatment plan. Early detection of TMD with suitable management may provide good response. This study was to relate demographic factors, signs and symptoms, diagnosis, stage of detection and treatment modalities on review outcome. Materials and Methods: 71 TMD patients were selected from Oral Medicine and Oral Pathology clinics. Patients’ details were recorded. Staging of patients was done based on guidelines by American Society of Temporomandibular Joint Surgeons (ASTMJS). Treatment modalities including selftherapy, occlusal splint and medication proposed to patients were based on their signs and symptoms. Prosthetic rehabilitation was indicated for free-end extension ridge. Treatment outcomes measure recommended by International Association of Oral and Maxillofacial Surgeons (IAOMS) was used during review visit. Results: Female showed higher incidence of TMD compared to male, with ratio of 2.5:1. 46(64.79%) patients were detected at early stage. Patients in their twenties [54(76.06%)] had the highest occurrence of TMD. Treatment modalities were correlated with signs and symptoms (p= 0.046), stage of detection (p= 0.030), and diagnosis (p= 0.023). Multiple regression displayed significant association on improvement of patients’ condition after treatment, mediated by stage of detection (r = - 0.216). 30(42.25%) patients detected at early stage had improvement of (on) signs and symptoms. Conclusion(s): Demographic factors contributed to incidence of TMD. Treatment plans were related to patients' condition, diagnosis and stage of detection. Early detection of TMD with proper management/s influenced patients’ condition.